PROSPECTS OF GREEN SUKUK FOR ENVIRONMENTAL FINANCING IN BRAZIL: A LEGAL AND SHARIAH PERSPECTIVE - Bruna Costa; Rafaela Lima; Thiago Rocha (Sharia Oikonomia Law Journal, 2025)
Brazil, as one of the world's most biodiverse countries, faces mounting environmental challenges requiring sustainable financing mechanisms aligned with global climate objectives. Green bonds have gained traction in Brazil, yet Shariah-compliant financial instruments remain largely unexplored, despite their global expansion. Green sukuk—Islamic bonds structured to finance environmentally beneficial projects—offer a unique opportunity to bridge Brazil’s sustainability goals with ethical finance practices grounded in Shariah principles. This study explores the legal and Shariah viability of introducing green sukuk as an alternative instrument for environmental financing in Brazil. Employing a qualitative legal research design, the study analyzes Brazil’s existing environmental finance framework, sukuk-related laws in key Islamic finance jurisdictions, and Shariah standards from bodies such as AAOIFI and IFSB. Interviews with Islamic finance scholars, legal experts, and Brazilian regulators supplement the doctrinal analysis. Findings indicate that while Brazil’s regulatory environment permits green financial instruments, legal reforms and institutional support would be necessary to accommodate Shariah-compliant structures. The study concludes that green sukuk could be a viable tool in Brazil’s sustainable finance arsenal, provided that cross-jurisdictional legal harmonization and Shariah alignment are proactively addressed.